PENGARUH BI-RATE DAN LOAN TO DEPOSIT RATIO (LDR) TERHADAP KREDIT BERMASALAH PADA BANK UMUM BUMN - Nanda Galuh Widiawati; Muhammad Faisal Abdullah (Program Studi Ekonomi Pembangunan, 2020)
This study aims to analyze the effect of the BI-Rate and Loan To Deposit Ratio (LDR) on Non Performing-Loans (NPL) at state-owned commercial banks. This study uses secondary data sources obtained using the documentation method. The samples in this study were 4 BUMN banks with saturated or census sampling techniques. The period used in this study was 15 years, from 2005 - 2019. The analysis technique used was Panel Data Regression.The results of the study simultaneously and partially show that the independent variable significantly influences the Non Performing Loan (NPL), the BI-Rate Variable has a significant positive effect on the probability amounting to 0.0119, while the Loan To Deposit Ratio (LDR) variable has a significant negative effect on the probability amounting to 0.0000.